Budapest building managers and the Holocaust in Hungary - Ádám, István Pál (The Holocaust and its contexts, 2016)
1. Building managers caught in the middle: the social history of Budapest concierges until 1943 -- 2. The concierges of the ghetto buildings -- 3. Building managers, bystanders and perpetrators -- 4. Turning the yellow star houses into protected houses -- 5. The building managers' role in rescue, and their ways to enrichment -- 6. Calling the building manager to account: the colourful palette of retribution in early post war Budapest from people's court to justificatory committee.